Pore-scale contact angle measurements at reservoir conditions using X-ray microtomography - Andrew,M; Bijeljic,B; Blunt,MJ (Advances in Water Resources, 2014)
Contact angle is a principal control of the flow of multiple fluid phases through porous media; however its measurement on other than flat surfaces remains a challenge. A new method is presented for the measurement of the contact angle between immiscible fluids at the pore scale at reservoir conditions (10 MPa and 50 °C) inside a quarry limestone through the use of X-ray microtomography. It is applied to a super-critical CO2–brine–carbonate system by resampling the micro-CT data onto planes orthogonal to the contact lines, allowing for vectors to be traced along the grain surface and the CO2–brine interface. A distribution of contact angles ranging from 35° to 55° is observed, indicating that the CO2–brine–carbonate system is weakly water-wet. This range of contact angles can be understood as the result of contact angle hysteresis and surface heterogeneity on a range of length scales. Surface heterogeneity is examined by comparison of micro-CT results with optical thin sections and SEM images.